Analisis Pengembangan Anti-Satelit Tiongkok Menurut Neo-Realisme Defensif - Riliani, Ni Putu Ginar; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2020): Jurnal Hubungan Internasional 2020, 2020)
This research aims to explain the reason of People’s Republic of China (PRC) in developing anti-satellite (ASAT) using qualitative research method. In 2007, PRC succeeded in ASAT trial by destroying their old weather satellite, Fengyun-1C.  PRC in its foreign politics strategy stated that PRC would contribute to create the world peace. Their statement was in contrast with ASAT launching. The launching of ASAT inflicts protests of other states, especially United States. Each of them has super power both in economic and military. PRC is known as the economic based-state, while at the other side also giving their attention towards the military. This research uses defensive neo-realism, and space control as the framework. This research found that, the main reason for PRC developing their ASAT is caused by the US’ attempt to dominate the space and also attempt to dominate full spectrum.     Keywords: China, anti-satellite (ASAT), Defensive Neo-realism, Space Control